Evolução da terminoliga princípio contábil baseada na Escola Norte-Americana - Oliveira, Atelmo Ferreira de (2003)
This research has as objective of study the evolution of the accountancy princliple terminology which is present in the accounting conceptual framework. The scene of this research will have as target the North American School of Accounting. The choice of the searched terminology is its relevance in the study of the Accounting Theory. To understand the evolution of the accountancy thought, will be boarded: the influence of the Feudal System and the Mercantilism in the European economic conception; the importance of the Industrial Revolution in the beginning of the accounting standards and the influence of England in the formation of the North American School of Accounting. With relation to U.S.A., the development of the economic-financial scene of the American society will be evaluated, focusing the contribution in the search of the construction of an applied theoretical framework to the Accounting. The economic-financial development of U.S.A. provided the sprouting of new users with specific necessities. The necessity of the user for useful information for the decision taking, unchained the process of research directed toward the establishment of an applied Accountancy terminology. In this process, the paper exerted for the responsible accountancy organisms for the accounting standards will be boarded, as well as the professionals associations which had invested in researches, aiming at to elaborate a body of accountancy principles and to adjust the accountancy procedures to the necessities of the users. To reach the research objective, a bibliographical revision in specialized literature will be effected, adopting the historical method, in the period that understands the development of the North American School of Accounting. As result of the research, it can conclude that the evolution process of the terminology which is studied presents a structural logical problem, because the impossibility of the construction of a theoretical framework, having as bases the principle terminology. The impossibility occurred in function of the reach attributed to the term, which made a difficult in its application in the elaboration of the accountancy procedures